Recent Findings in the Posttranslational Modifications of PD-L1 - Li, Shu-Man (J Oncol, 2020)
Immune checkpoint therapy, such as the reactivation of T-cell activity by targeting programmed cell death 1 (PD-1) and its ligand PD-L1 (also called B7-H1 and CD274) has been found pivotal in changing the historically dim prognoses of malignant tumors by causing durable objective responses. However, the response rate of immune checkpoint therapy required huge improvements. It has been shown that the expression of PD-L1 on cancer cells and immune cell membranes is correlated with a more durable objective response rate to PD-L1 antibodies, which highlights the importance of deeply understanding how this protein is regulated. Posttranslational modifications such as phosphorylation, N-glycosylation, and ubiquitination of PD-L1 have emerged as important regulatory mechanisms that modulate immunosuppression in patients with cancer. In this review, we summarized the latest findings of PD-L1 protein modification and their clinical applications.